Impact of pre-existing comorbidities on outcomes of patients undergoing surgical aortic valve replacement – rationale and design of the international IMPACT registry - Bakhtiary, Farhad; Ahmad, Ali El-Sayed; Autschbach, Ruediger; Benedikt, Peter; Bonaros, Nikolaos; Borger, Michael; Dewald, Oliver; Feyrer, Richard; Geissler, Hans-Joachim; Gruenenfelder, Juerg; Lam, Ka Yan; Leyh, Rainer; et al. (Journal of Cardiothoracic Surgery, 2021)
Background: Degenerative aortic valve disease accounts for 10–20% of all cardiac surgical procedures. The impact of pre-existing comorbidities on the outcome of patients undergoing surgical aortic valve replacement (SAVR) needs further research. Methods: The IMPACT registry is a non-interventional, prospective, open-label, multicenter, international registry with a follow-up of 5 years to assess the impact of pre-existing comorbidities of patients undergoing SAVR with the INSPIRIS RESILIA aortic valve on outcomes. IMPACT will be conducted across 25 sites in Austria, Germany, The Netherlands and Switzerland and intends to enroll approximately 500 patients. Patients will be included if they are at least 18 years of age and are scheduled to undergo SAVR with the INSPIRIS RESILIA Aortic Valve with or without concomitant ascending aortic root replacement and/or coronary bypass surgery. The primary objective is to determine all-cause mortality at 1, 3, and 5 years post SAVR. Secondary objectives include cardiac-related and valve-related mortality and structural valve deterioration including hemodynamics and durability, valve performance and further clinical outcomes in the overall study population and in specific patient subgroups characterized by the presence of chronic kidney disease, hypertension, metabolic syndrome and/or chronic inflammation. Discussion: IMPACT is a prospective, multicenter European registry, which will provide much-needed data on the impact of pre-existing comorbidities on patient outcomes and prosthetic valve performance, and in particular the performance of the INSPIRIS RESILIA, in a real-world setting. The findings of this study may help to support and expand appropriate patient selection for treatment with bioprostheses. Trial registration: ClinicalTrials.gov identifier: NCT04053088.
CRIS-Team Scopus Importer:2022-05-03
Keywords: Aortic valve disease; Comorbidities; Real-world setting; SAVR; Surgical aortic valve replacement